2020
DOI: 10.1155/2020/5915034
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of High‐Strength Steel Fiber Lightweight Aggregate Concrete on Mechanical Properties and Toughness Index

Abstract: In this paper, three different kinds of steel fibers, being micro (M), end-hooked (H), and corrugated (C), commonly used in engineering applications, are added to high-strength lightweight aggregate concrete (HLAC) to study the effects of steel fiber and volume content ratio of fiber on the compressive, splitting tensile, and flexural strength of HLAC. The range of steel fiber volume content fraction studied is 0.5% to 2.0%. The research shows that different types of steel fiber have different effects on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Existen investigaciones sobre su implementación en la mezcla de hormigón liviano de alta resistencia y cómo influyen en esta, así como también sobre la relación de contenido de volumen de la fibra en la resistencia a la tracción por división, a la flexión y a la compresión. Teniendo principalmente el rango de fracción de contenido de volumen de fibra de acero estudiado de 0,5 % a 2,0 %, se observa que los diferentes tipos de fibra de acero influyen de diferente manera en la mezcla, y la microfibra de acero es la que tiene mejor tenacidad sobre las otras dos [59].…”
Section: Análisisunclassified
“…Existen investigaciones sobre su implementación en la mezcla de hormigón liviano de alta resistencia y cómo influyen en esta, así como también sobre la relación de contenido de volumen de la fibra en la resistencia a la tracción por división, a la flexión y a la compresión. Teniendo principalmente el rango de fracción de contenido de volumen de fibra de acero estudiado de 0,5 % a 2,0 %, se observa que los diferentes tipos de fibra de acero influyen de diferente manera en la mezcla, y la microfibra de acero es la que tiene mejor tenacidad sobre las otras dos [59].…”
Section: Análisisunclassified
“…The micro-steel fibers utilized in their study had dimensions of 11 mm in length and 0.2 mm in diameter. Ye et al [30] prepared specimens of micro-fine steel fiber-high-strength lightweight aggregate concrete (MSFHLAC) using micro-fine steel fibers of 13 mm in length and 0.2 mm in diameter, high-strength shale aggregate, and mineral admixtures. They assessed the influence of micro-fine steel fiber volume fraction, sand ratio, and the water-cement ratio on the static mechanical properties, including compressive strength, splitting tensile strength, flexural strength, shear strength, and the flexural toughness of MSFHLAC specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Steel fiber reinforced cementitious composite (SFRCC) has excellent mechanical properties and deformation properties [8], in ambient temperature, steel fiber can improve the flexural tensile strength and flexural toughness of the matrix obviously, as well as it is an excellent material for improving the seismic performance and durability of engineering structures [9,10]. Rostásy and Sprenger [11] studied the compressive and tensile properties of steel fiber reinforced concrete (SFRC), and the results showed that adding steel fiber could significantly reduce the concrete damage caused by temperature decrease.…”
Section: Introductionmentioning
confidence: 99%